Ground improvement geosystems densification and reinforcement : proceedings of the Third International Conference on Ground Improvement Geosystems London, 3-5 June 1997 - Davies, M. C. R.; Schlosser, Francois (Thomas Telford, 1997)
The papers presented in this volume describe developments from around the world on ground improvement by densification and reinforcement. Numerous case studies show how new and improved methods have actually been applied over a wide variety of ground conditions.
Published on behalf of the British Geotechnical Society.
Keywords: Soil stabilization -- Congresses.; Engineering geology -- Congresses.; elektronické knihy; electronic books